Shape and Size Variation in Elapid Snake Fangs and the Effects of Phylogeny and Diet - Alessandro Palci; Michael S. Y. Lee; Jenna M. Crowe-Riddell; Emma Sherratt (Evolutionary Biology, 2023)
Recent studies have found correlations between the shape of snake teeth/fangs and diet. These studies were done at a very broad phylogenetic scale, making it desirable to test if correlations are still detectable at a narrower evolutionary scale, specifically within the family Elapidae. To this end, we studied fang shape in a dense selection of elapids representing most genera worldwide (74%). We used three-dimensional geometric morphometrics to analyse fang diversity and evaluate possible correlations between fang shape, fang size, and diet. We detected weak phylogenetic signal for both shape and absolute fang size, and found that evolutionary allometry contributes a small proportion of the among-species variation. The distribution of elapid fangs in morphospace was found to be surprisingly conservative, with only a few outliers. The only three dietary categories that were found to have a significant effect on fang shape are mammals, lizards, and reptile eggs, with mammals having a significant effect also on absolute but not relative fang size. Our results show that there are disparate patterns in fang-diet relationships at different evolutionary scales. Across all venomous snakes, previous work found that fangs are strongly influenced by diet, but within elapids our study shows these same associations are weaker and often non-significant. This could result from limitations in these types of studies, or could reflect the fact that elapids are a relatively young clade, where recent extensive divergences in diet have yet to be mirrored in fang shape, suggesting a lag between changes in ecology and dental morphology.

Phototactic tails: Evolution and molecular basis of a novel sensory trait in sea snakes - Jenna M. Crowe‐Riddell; Bruno F. Simões; Julian C. Partridge; David M. Hunt; Steven Delean; Julian G. Schwerdt; James Breen; Alastair Ludington; David J. Gower; Kate L. Sanders (Molecular Ecology, 2019)
Dermal phototaxis has been reported in a few aquatic vertebrate lineages spanning fish, amphibians and reptiles. These taxa respond to light on the skin of their elongate hind‐bodies and tails by withdrawing under cover to avoid detection by predators. Here, we investigated tail phototaxis in sea snakes (Hydrophiinae), the only reptiles reported to exhibit this sensory behaviour. We conducted behavioural tests in 17 wild‐caught sea snakes of eight species by illuminating the dorsal surface of the tail and midbody skin using cold white, violet, blue, green and red light. Our results confirmed phototactic tail withdrawal in the previously studied Aipysurus laevis , revealed this trait for the first time in A. duboisii and A. tenuis , and suggested that tail photoreceptors have peak spectral sensitivities between blue and green light (457–514 nm). Based on these results, and an absence of photoresponses in five Aipysurus and Hydrophis species, we tentatively infer that tail phototaxis evolved in the ancestor of a clade of six Aipysurus species (comprising 10% of all sea snakes). Quantifying tail damage, we found that the probability of sustaining tail injuries was not influenced by tail phototactic ability in snakes. Gene profiling showed that transcriptomes of both tail skin and body skin lacked visual opsins but contained melanopsin ( opn4x ) in addition to key genes of the retinal regeneration and phototransduction cascades. This work suggests that a nonvisual photoreceptor (e.g., Gq rhabdomeric) signalling pathway underlies tail phototaxis, and provides candidate gene targets for future studies of this unusual sensory innovation in reptiles.

Future Directions in the Research and Management of Marine Snakes - Vinay Udyawer; Peter Barnes; Xavier Bonnet; François Brischoux; Jenna M. Crowe-Riddell; Blanche D’Anastasi; Bryan G. Fry; Amber Gillett; Claire Goiran; Michael L. Guinea; Harold Heatwole; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)